Judging the unseen: The impact of onset controllability in shaping perceptions of defendants with traumatic brain injury - Claire Williams; Inesa Ledovskyte (PLoS ONE, 2025)
Traumatic brain injury (TBI) has been associated with increased risk of criminality, yet very little is known about how individuals with TBI may intersect with the adjudication phase of the criminal justice system. Therefore, the aim of this study was to conduct the first empirical investigation of how individuals with TBI are perceived within the context of a UK magistrates’ court, and how the perceived controllability of the onset of injury may influence perceptions and sentencing-related recommendations. 174 participants (60.35% female, mean age = 34.86 years) from a general population sample, reflecting diverse employment and education backgrounds, read a fictional transcript of a magistrate sentencing a defendant for an assault charge. Participants were randomly allocated to a single condition (Onset Controllable, Onset Uncontrollable, or no-TBI control), where the onset controllability of the injury was experimentally manipulated. Participants were asked to make sentence related recommendations and to rate the defendant’s level of risk and dangerousness, behavioural tendencies, and the extent to which they felt empathy/sympathy towards them. Additionally, their proximity to, knowledge of, and attitudes towards brain injury were assessed. The perceived onset controllability of the TBI was not found to influence perceptions and sentencing-related recommendations. Instead, participants reported feeling more empathetic towards the defendant and rated their behavioural tendencies more favourably if they were described as having sustained a TBI, irrespective of its onset controllability. This suggests that the presence of TBI might evoke strong empathic responses that counteract the tendency to assign blame based on controllability and may also lead to more favourable behavioural perceptions, but that such evaluations are not strong enough to exert an influence on sentencing related recommendations. Consequently, it is possible that the invisible nature of TBI-related disability, coupled with poor public understanding, may mean that information about a defendant’s brain injury is overlooked and/or not taken into full account in sentencing related recommendations.